Study protocol of an early randomized intervention trial assessing the metabolic effects of two levels of exercise intensity in children undergoing cancer treatment: the APACIS study - Justine Thomas; Thomas Filleron; Françoise Auriol; Claire Laurens; Marlène Pasquet (BMC Cancer)
Abstract Background Insulin sensitivity is a key factor of the development of metabolic diseases, highly prevalent in adult survivors of childhood cancers. The aim of the Adapted Physical Activity for children treated for Cancer and Insulin-Sensitivity (APACIS) study is to investigate the effects of two exercise programs started as early as diagnosis on metabolic profile and physical health. Methods APACIS is a trial that includes children at diagnosis of all pediatric cancers which are randomly allocated to the Soft group – for low intensity physical activity – or to the Strong group – for mixed, high intensity exercise. Both programs are done at least twice weekly for 30 to 60 min over 6 months, adapted to the health status of the children, with a follow-up of 18 months. The primary objective is the change in insulin sensitivity measured by the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) at 0, 3, 6, 12 and 24 months between the two groups. The secondary objectives include changes in cholesterol, triglycerides and cortisol blood levels, state of undernourishment, cardiorespiratory fitness (based on peak rate of oxygen uptake of the 6 Minute Walk Test), flexibility (sit and reach flexibility test), fat mass distribution (Waist-to-Hip Ratio) and level of physical activity assessed by questionnaire at 0, 3, 6, 12 and 24 months. On-therapy metabolic adaptation in the different patient groups will also be evaluated by an integrated pipeline combining the detection of 150 metabolites, with metabolic pathway enrichment and network mapping. This approach will be complemented by an analysis of intestinal and oral microbiota, to identify the species impacted by treatments and the influence of exercise on these toxicities. Discussion The APACIS study investigates the metabolic, motor, and nutritional effects in children with cancers performing low versus high intensity exercise with an innovative approach consisting of early practice since diagnosis. It will contribute to better personalize physical activity prescription during treatment of pediatric cancers. Trial registration The study has been registered on ClinicalTrials.gov (NCT05383092) the 7 of November, 2022.